The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/cncr.26342
|View full text |Cite
|
Sign up to set email alerts
|

Identification and assessment of new biomarkers for colorectal cancer with serum N‐glycan profiling

Abstract: BACKGROUND:The objectives of this study were to identify and validate the diagnostic value of N-glycan markers in colorectal cancer (CRC) and to uncover their underlying molecular mechanism. METHODS: In total, 347 individuals, including patients with CRC, patients with colorectal adenoma, and healthy controls, were divided randomly into a training group (n ¼ 287) and retrospective validation groups (n ¼ 60). Serum N-glycan profiling was analyzed by DNA sequencer-assisted/flurophore-assisted carbohydrate electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 28 publications
4
47
0
Order By: Relevance
“…DSA-FACE is a simple and efficient technology for measuring N-glycan changes in serum. We previously used the technology to assist in the diagnosis of HCC, CRC, and gastric cancer [29][30][31]. The study was designed to target analysis of the aberrant N-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…DSA-FACE is a simple and efficient technology for measuring N-glycan changes in serum. We previously used the technology to assist in the diagnosis of HCC, CRC, and gastric cancer [29][30][31]. The study was designed to target analysis of the aberrant N-glycans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased sialylation (mainly derived from α-2,3-linked sialic acid) of serum proteins was confirmed by MAL II-binding lectin blot analysis in LCMM patients. The decreased core-fucosylation has also been reported in colorectal cancer, gastric cancer and breast carcinoma, and an increase in sialylation was also found in breast cancer [19, 3233]. Recently, Glavey SV et al reported that high expression of ST3GAL6, an α-2,3-linked sialyltransferase, could influence homing and survival in multiple myeloma [34].…”
Section: Discussionmentioning
confidence: 99%
“…DSA-FACE, which we applied in this study, provides a convenient, non-invasive, excellent sensitive method to detect desialylated N-glycan profiling in serum and may be more practical for routine clinical analysis. This technique was previously used to assist in the diagnosis of various cancers, such as Hepatocellular Carcinoma (HCC), colorectal cancer and gastric cancer [19,20,27]. As we have mentioned before, SPE and IFE are poor at detecting free light chains.…”
Section: Discussionmentioning
confidence: 99%
“…Serum glycomic studies to discover novel glycan cancer biomarkers have been highlighted (Adamczyk et al 2012 ). Numerous glycan tumor marker candidates for various cancers, including liver (Kaji et al 2013 ;Kamiyama et al 2013 ;Wu et al 2012 ;Tang et al 2010 ;Goldman et al 2009 ;Comunale et al 2009 ;Tanabe et al 2008 ;Ressom et al 2008 ), ovary (Biskup et al 2013 ;Hua et al 2013 ;Alley et al 2012 ;Abbott et al 2010 ;Leiserowitz et al 2008 ), pancreas (Li et al 2009 ;Okuyama et al 2006), breast (de Leoz et al 2011Alley et al 2010 ;Zeng et al 2010 ;Storr et al 2008 ;Abd Hamid et al 2008 ;Kyselova et al 2008 ;Kirmiz et al 2007 ), prostate , lung (Arnold et al 2011 ), colorectum (Zhao et al 2012 ), bile duct (Silsirivanit et al 2011 ), and esophagus ) cancers, have been reported. Most of these glycomic analyses have been carried out by newly developed high-throughput platform technologies, such as mass spectrometry-based methods and lectin-based methods, which have enabled the effi cient analysis of large cohorts of samples.…”
Section: Glycomic Studies On Serum Of Cancer Patientsmentioning
confidence: 99%